PENGARUH TAPAK LIMAN (Elephantopus scaber) TERHADAP INTENSITAS DISMENORE PADA REMAJA PUTERI - Fajrin, Dessy Hidayati; Kurniatin, Lydia Febri; Siswina, Tessa (Poltekkes Kemenkes Pontianak, 2024)
Menstrual pain (dysmenorrhea) can have an impact on the activities or activities of women, especially teenagers. If dysmenorrhea is not treated immediately, it will affect the mental and physical function of the individual, it is urgent to take pharmacological or non-pharmacological action immediately. One of the plants that can be used as traditional medicine is Tapak Liman (Elephantopus scaber). Tapak Liman contains the flavonoid luteolin-7-glikosida stigmasterol, isodeoxyelephantopin, elephantopin, deoxyelephantopin, epiprielinol which have natural analgesic and anti-inflammatory effects. Dysmenorrhea is one example of visceral pain, namely pain that is very complex, Tapak Liman is believed to have chemical components that are antioxidants and sedatives aromatherapy to calm and relax. In this study, researchers used quantitative research. The method used was quasi-experimental with one group pretest-posttest design. The research instrument was a questionnaire on the respondent's level of knowledge and measurement of pain intensity using the Wong Baker Rating Scale. Based on the results of non-parametric analysis with the Wilcoxon Test, the results of the Z test are -5,476 with a probability of 0.000. If the probability = 5% (level of significance) then H1 is accepted, it can be concluded that there is a significant effect on giving Tapak Liman as aromatherapy to reduce the intensity of dysmenorrhea pain in Midwifery students, Poltekkes, Pontianak Ministry of Health. The average decrease in the intensity of dysmenorrhea pain obtained before the intervention was 5.1788 and 3.3455 was obtained after the intervention.